Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Prostate Cancer 2021
DOI: 10.36255/exonpublications.prostatecancer.p53.2021
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Role of p53 in Prostate Cancer

Abstract: Mutations in the tumor suppressor gene TP53 are among the most common genetic aberrations in cancer. In prostate cancer, the role of mutant TP53 remains incompletely understood. Initially, mutations in TP53 were considered late events during malignant progression and associated with metastatic dissemination and castration resistance. However, recent studies report an inactivation of TP53 at an unexpectedly high frequency in primary as well as metastatic castration-naïve prostate cancer. In this chapter, we dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 82 publications
2
17
0
1
Order By: Relevance
“…Overall, our analyses are consistent with previous findings of moderate-to-low frequency of TP53 mutations in primary PC [ 13 ]. Relative to normal prostate, we found MDM4 expression to be elevated in PC, with the highest trend observed in mutant p53 PC samples.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Overall, our analyses are consistent with previous findings of moderate-to-low frequency of TP53 mutations in primary PC [ 13 ]. Relative to normal prostate, we found MDM4 expression to be elevated in PC, with the highest trend observed in mutant p53 PC samples.…”
Section: Resultssupporting
confidence: 92%
“…The tumour-suppressive capacity of p53 is frequently lost in PC by direct mutation [ 8 , 10 , 34 ]. TP53 mutation frequency increases (>70%) with progression to lethal metastatic PC (reviewed [ 13 ]). In PCs that retain wt p53, we hypothesized that its activities are compromised by deregulation of its key negative regulators, MDM2 and MDM4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Xu et al reported a significantly shorter DFS in patients with TP53 mutated compared to wild-type TP53 ( n = 34, p = 0.003) [ 44 ]. Mutations in TP53 are among the most frequent somatic aberrations in human cancers and are frequently reported as a negative prognostic factor for survival in many solid tumour types, including lung [ 45 ], colorectal [ 46 ], breast [ 47 ], and prostate carcinoma [ 48 ], irrespective of systemic therapy. The impact of somatic pathogenic variants on the treatment outcomes of TETs should be further evaluated in patient cohorts large enough for multivariate analysis considering histopathology, stage, and treatment regimen.…”
Section: Discussionmentioning
confidence: 99%